ANALISA EKONOMI RANCANGAN PLTS OFF-GRID PADA ADIDAYA WORKSHOP - Putra Ariantika, I.P. Dika; Setiawan, I.N.; Sukerayasa, I.W. (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUM, 2023)
The PLTS Off-Grid design at the Adidaya Workshop as an additional power supplier is based on the load needs used for the equipment and operational on the workshop. PLTS Off-Grid features are economically likely to take a long time to make a profit. This study deals with the economic analysis of the PLTS Off-Grid system design using the Net Present Value (NPV) analysis method and aims to find out the comparison projections between output and output of the Off-Grid PLTS project at the Adidaya Workshop during the estimated life of PLTS will operate over 20 years. After the calculation, it was obtained that 1th Scenario using a variation of the solar panel capacity of 300 Wp with a battery of 540 Ah produced the largest RAB demand value worth Rp. by 286.038.441 While the smallest RAB requirement value is generated from 4th Scenario using a variation in solar panel capacity of 300 Wp with a 540 Ah battery worth Rp 252.093.730. The largest and the smallest NPV values are also generated by 1th and 4th Scenario with the NPV value of -Rp 316.734.509 and –Rp 251.285.665.